Impletentasi Konsep Pendidikan Akhlak Luqmanul Hakim di Era Society 5.0: Kajian Tafsir Al-Misbah - Machmud; Mahmudi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Humans as creatures who can be educated and educated (homo educandum) are implemented in educational activities in which there are educators and students as the main objects of education. Students from an educational perspective are often referred to as immature people, so they need help from other people who are considered adults. This process of assistance is called education (Daradjat 2006). The most basic education grows from the family environment, because it is from the family that the nation's next generation of children grows. The growth of a child's attitudes and behavior depends on the parents' educational patterns, especially how parents prepare their children in the Society 5.0 era, which has both positive and negative impacts on their lives. In fact, Islam has its own concept in educating children, but due to increasingly rapid technological developments, parents are paying less attention to educating children, especially educating a child's morals. The concept of moral education recommended by Islamic law is contained in the Koran, Surah Luqman, verses 12-19. The aims of this research are: 1) To find out who Luqmanul Hakim is in the Koran; 2) To find out Luqmanul Hakim's message about moral education according to the interpretation of Muhammad Quraish Shihab in the Al-Misbah tafsir and Mustafa Al-Maraghi in the Al-Maraghi tafsir 3) How is it implemented in the Era of Society. This research uses qualitative research with the type of library research. The data sources used are primary data sources which are the main data sources directly related to the research object including: QS Luqman verses 12-19 and their translations, Al Misbah's interpretation and Al Maraghi's interpretation then secondary data sources which include: journals, hadith and books -books that support and complement primary data. The data analysis used is a descriptive method. The research results show that: 1) Luqmanul Hakim is a noble servant of Allah and was chosen as a role model in educating children; 2) so that when educating children, it should be based on full love for their children by giving advice in the form of faith, monotheism and muamalah. These advices will lead their children to become noble, knowledgeable young people with a nation and state. noble morals too; 3) The importance of Moral Education in the Society 5.0 era as a bulwark for using technology as expected.